Linguistic Accommodation and Intercultural Communication as Imperatives to Convey Malukat Rituals - Ni Nyoman Kertiasih; Made Subur; Anak Agung Inten Mayuni (Yayasan Rumah Peneleh, 2023)
This paper aims to examine the linguistic accommodation of the tour guides for foreign tourists at the Taman Beji Griya as they daily face problems not being native speakers of a foreign language, yet have obligations to provide information and understanding to foreign tourists. Taman Beji Griya has two main attractions which are nature and the Hindu religious rituals, namely Malukat. This study employed a qualitative method with an approach to linguistic accommodation and intercultural communication. The data were collected by listening and recording, interviews, and observing the activities in terms of communication between tour guides and foreign tourists, and then analysed interpretively through the process of data reduction, presentation, and verification. This study shows that the linguistic accommodation of tour guides at Taman Beji Griya is convergent with English-speaking foreign tourists, divergent with tourists who cannot speak English well, and not being over-accommodated. Convergent linguistic accommodation enables the tourist to gain valuable knowledge and experience during their activities. Further, tourists generally understand language barriers and try to build their own impressions and experiences about the objects and activities carried out. This study recommends improving the language skills of tour guides through the recruitment of professional tour guides who are able to speak English and other foreign languages, as well as continuing their education and training.